Titus Brandsma: Getuige van God - J.M. Bos (Acta Theologica)
“Can I help it that in all things God gives witness to himself?” This quote of Titus Brandsma shows his concept of God. This article reflects on the way in which Blessed Titus Brandsma gave witness to God from three perspectives: his mystical theology, his social engagement, and his way of the cross. Brandsma defines mysticism as a particular unification of God and man, whereby the latter becomes conscious of God’s presence and, on his part, also unifies himself with God. His writings highlight three key aspects of mysticism that are closely related: mysticism is two-sided, nearby, and embodied. Titus Brandsma was primarily active in the fields of education and journalism. He analysed the contemporary social and political situation and was very critical of national socialism, especially because its basic values were in conflict with the Christian value of love. He regarded the spiritual crisis as more fundamental than the social and economic crises. He offered a new concept of God, which was founded on God’s presence in the core of everybody, as a reply to individualism and social exclusion. Finally, this article gives some examples showing the way in which Brandsma gave witness of God during the final months of his life. Brandsma was imprisoned because of his effort for the resistance of the Catholic press against national socialism. Testimonies show that Brandsma could experience God’s presence nearby. This helped him remain strong spiritually.